The role of nanosilver in improving frequency of single cell formation of Limonium sinuatum (L.) Mill - Cuong, Do Manh; Long, Le Thanh; Tung, Hoang Thanh; Luan, Vu Quoc; Hien, Vu Thi; Linh, Nguyen Thi Nhat; Phuong, Truong Thi Bich; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
In this research, nanosilver with different concentrations and treatment time was used to sterilize infection agents and induce initial explants which were used as materials for cell suspension culture of Limonium sinuatum. The result showed that leaf explants sterilized with 0.2 g/L nanosilver for 20 minutes had highest effect (live rate 73.33%) comparing to HgCl2and Ca(ClO)2(56.66% and 64.44%, respectively). In addition, the leaf explants which were treated with nanosilver and cultured in ½ MS medium supplemented with 20 g/L sucrose, 1 mg/L picloram and 2.5 g/L gelrite also induced calli (friable calli, milk white color, embryogenic callus structure). Moreover, cell suspension formation process from these calli was also observed highest on the 20thday (49,088 cells/mL) in liquid shaking culture condition comparing to control treatment (19,361 cells/mL) when they were cultured on similar medium combined with 1.2 mg/Lnanosilver. These cells had the best growth, development and regeneration from the 16thday to the 20thday. The ability of shoot and callus regeneration was highest (67.77%) in ½ MS medium which was supplemented with 20 g/L sucrose, 1 mg/L zeatin, 2.5 g/L gelrite and 1.6 mg/L nanosilver compared with control treatment having no nanosilver (40.00%). This research showed that in micropropagation of Limonium sinuatum, nanosilver was proved to be an effective agent for sterilization, explant induction, cell suspension origination, and callus and shoot regeneration. Beside that, nanosilver had negative impact on the development of explants when it was used with high concentration for extended period.